Survey of wireless channel measurement and characterization for high-speed railway scenarios - Liu LIU; Cheng TAO; Hou-jin CHEN; Tao ZHOU; Rong-chen SUN; Jia-hui QIU (Tongxin xuebao)
The conducted measurement campaigns,domestic and overseas,were presented.Meanwhile,proposals and standard channel models from the international standardization organization were reviewed.The large-scale and small-scale fading characteristics of High-Speed Railway wireless channels were adequately compared,and it is found that the channel parameters depend on the propagation environment and the distance between the transmitter and receiver.Moreover,due to difficulties encountered in realistic channel measurements,theoretical channel characterization methods were analyzed.Finally,open research issues were presented.